The perceptions of people with low back pain treated in the Spanish National Health, and their experience while undergoing a new evidence-based treatment. A focus group study. (September 2014) - Cano, Alejandra; Gestoso, Mario; Kovacs, Francisco; Hale, Claire; Mufraggi, Nicole; Abraira, Víctor
Abstract Purpose: To explore the perceptions of people with low back pain (LBP) treated within the Spanish National Health Service, and their experience while undergoing a new evidence-based treatment ("neuroreflexotherapy"). Methods: A focus group (FG) study was conducted. Participants were divided into five groups according to whether they: suffered from subacute versus chronic LBP; had undergone one versus several neuroreflexotherapy procedures; showed a clinically relevant improvement in pain and disability according to validated measuring instruments, and reported it. Thirty-two patients were selected by purposive sampling. Content analysis was undertaken by two researchers who had no contact with the clinicians. Results: Subacute and chronic LBP curtails daily activities, reduces quality of life (QoL) and self-esteem, and is experienced as a stigma. Patients want to be treated with respect and empathy by clinicians who refrain from judging them. New treatments trigger hope, but also fear and mistrust. Most patients experiencing a clinically relevant improvement resume daily activities, and report improvement in QoL, self-esteem and emotional wellbeing. Conclusion: Southern European LBP patients have similar perceptions to those in other cultural settings. LBP jeopardizes patients' QoL and self-esteem. When pain improves significantly, patients are happy to acknowledge it and resume their normal life. Implications for Rehabilitation People with low back pain (LBP) want to be treated with respect and empathy by clinicians who inspire confidence and refrain from judging them. When faced with a new evidence based treatment, people with subacute and chronic LBP are hopeful, but apprehensive. Most of those who experience a clinically meaningful improvement after treatment are happy to acknowledge it and resume an active and fulfilling life. People who report no improvements after being treated, should be believed.